Особливості правового регулювання реалізації права на працю працівниками закладів вищої освіти : автореферат дисертації - Рижеченко, К. С.; Ryzhechenko, K. S.; Могілевський, Л. В. - науковий керівник (Харків : Харківський національний університет внутрішніх справ, 2020)
У дисертації наведено теоретичне узагальнення і нове вирішення наукового завдання – визначення сутності та особливостей правового регулювання реалізації права на працю працівниками закладів вищої освіти, а також виробленню пропозицій щодо шляхів удосконалення загального трудового та спеціального законодавства в цій сфері. У результаті проведеного дослідження сформульовано ряд висновків, пропозицій та рекомендацій, спрямованих на досягнення поставленої мети.

The dissertation research is focused on determining specific features of legal regulation of realizing the right to labor by the employees of higher educational institutions. The author of the dissertation has provided theoretical generalization and a new solution to the scientific problem, which is to determine the nature and specific features of legal regulation of realizing the right to labor by the employees of higher educational institutions, as well as to develop propositions and recommendations for improving the relevant general and special labor legislation. The historical and legal analysis of the formation and development of legislation in the field of legal regulation of labor of the employees of higher educational institutions has been carried out. It has been established that an employee is an individual who has labor legal capacity and who has entered into an individual employment contract with the employer, on the basis of which he directly performs a certain job function. The author has suggested own definition of the concept of the right to labor of the employees of higher educational institutions, and has determined its most characteristic features. It has been substantiated that the key principles of legal regulation of the work of the employees of higher educational institutions are unity and differentiation. The author has carried out the classification of guarantees for realizing the right to labor by the employees of higher educational institutions, which are offered to be divided into two groups: 1) depending on the range of persons, who are the subjects of the guarantees; and 2) depending on the stage of realizing the right to labor. It has been stated that the current Ukrainian legislation on higher education issues undergone significant changes and transformations, but it still has problematic aspects, in particular in terms of regulating labor of employees of higher educational institutions. It has been stated that there have recently been positive changes in this direction in Ukraine, but these principles have not received the full implementation in our country. This has a negative effect both on the realization of labor rights and legitimate interests by the employees, who are under study, and the prestige of the working career in the whole.

В диссертации приведено теоретическое обобщение и новое решение научной задачи – определение сущности и особенностей правового регулирования реализации права на труд работниками высших учебных заведений, а также выработке предложений о путях совершенствования общего трудового и специального законодательства в этой сфере. В результате проведенного исследования сформулирован ряд выводов, предложений и рекомендаций, направленных на достижение поставленной цели.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Specific Features of Legal Regulation for Realizing the Right to Labor by the Employees of Higher Educational Institutions
Keywords: Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00. 05; 081 - Право; Україна; історико-правовий аналіз; правове регулювання; заклад вищої освіти; працівник; право на працю; трудове законодавство; оплата праці; робочий час; нормування праці; час відпочинку; зарубіжний досвід; трудові правовідносини; Ukraine; historical and legal analysis; higher educational institution; employee; labor legislation; right to labor; legal regulation; payment for labor; working hours; labor norming; foreign experience; labor relations; Украина; историко-правовой анализ; работник; учреждение высшего образования; трудовое законодательство; право на труд; правовое регулирование; оплата труда; рабочее время; нормирования труда; время отдыха; зарубежный опыт; трудовые правоотношения